Uncertainties of glacial isostatic adjustment model predictions in North America associated with 3D structure - Li, Tanghua (2020)
We quantify GIA prediction uncertainties of 250 1D and 3D glacial isostatic adjustment (GIA) models through comparisons with deglacial relative sea‐level (RSL) data from North America and rate of vertical land motion ( urn:x-wiley:00948276:media:grl60497:grl60497-math-0001) and gravity rate of change ( urn:x-wiley:00948276:media:grl60497:grl60497-math-0002) from GNSS and GRACE data, respectively. Spatially, the size of the RSL uncertainties varies across North America with the largest from Hudson Bay and near previous ice margins along the northern Atlantic and Pacific coasts, which suggests 3D viscosity structure in the lower mantle and laterally varying lithospheric thickness. Temporally, RSL uncertainties decrease from the Last Glacial Maximum to present except for west of Hudson Bay and the northeastern Pacific coast. The uncertainties of both these regions increase from 30 to 45 m between 15 and 11 ka BP, which may be due to the rapid decrease of surface loading at that time. Present‐day urn:x-wiley:00948276:media:grl60497:grl60497-math-0003 and urn:x-wiley:00948276:media:grl60497:grl60497-math-0004 uncertainties are largest in southwestern Hudson Bay with magnitudes of 2.4 mm/year and 0.4 μGal/year, mainly due to the 3D viscosity structure in the lower mantle.